PENGEMBANGAN E-MODUL BERBASIS FLIPBOOK DENGAN CASE METHOD PADA MATA KULIAH PENGUJIAN KENDARAAN : Validitas Ahli - Kelana, Ananda Jaka; Dedy Irfan; Hasan Maksum; Rizky Ema Wulansari; Efrizon (Journal for Lesson and Learning Studies, 2022)
The rapid development of ICT (Information and Communication Technology) affects various aspects of human life including education. Utilizing this information technology can support the independent learning process for the better. E-module with the case method model is suitable media implementing in  Technology and Vocational Education. This study aims to analyse the validity of E-module with case method in vehicle testing course the expert before being implemented in the learning process. This study used a quantitative research in the form of a survey. The validity of this research is divided into two categories, namely design validity and material validity. Data collection is using questionnaire in a form of Likert scale with five possible answers is used in this media validation questionnaire. The data analysis in this study is use level of validity according to Formula V Aiken. Based on the results of the study, it can be concluded that media design is valid in terms of didactic, construction and technical aspects. While the results of material validation also show that the material in the media is valid in terms of the quality of the material and the quality of learning. It can be concluded that the flipbook-based e-module with the case method used in this course is effective as a learning medium in the classroom during the learning process.